Informality as de-regulation of the state. The twilight zones of the post-colonial city - Rodríguez Rivero, Luis (2021)
What we understand as informality existed a long time before the term was coined. For a better understanding of the phenomenon, it is necessary to trace the origins of those activities that over time have been carried outside the legal system that formally defines the modern nation-state. The article seeks to articulate the contemporary informal phenomenon to other ways of existing outside the law that have their origin in colonial regimes, characterized by the need to implement parallel government and legal systems. It is about understanding informality as a phenomenon typical of postcolonial situations and proposing ways out from that reading.